IMPLEMENTATION OF THE SELF-ASSESSMENT SYSTEM FOR ARTICLE 21 OF THE HARMONIZED UUD INCOME TAX AT THE WIN PARTNERS TAX CONSULTANT OFFICE, MAKASSAR BRANCH - Alan Syawaluddin; Muhammad Akbardin; Andi Sugeng Sapta Aji (Universitas Ichsan Sidenreng Rappang, 2025)
The purpose of this study was to determine whether the Implementation of the Self Assessment System has been effective based on the Harmonized Constitutions in the Calculation of Income Tax Article 21 at the Win Partners Office, Makassar Branch. The analysis method used by the author is a qualitative descriptive method. According to Sugiyono (2022), the qualitative descriptive method is a research method based on the philosophy of postpositivism used to research natural object conditions (as opposed to experiments) where the researcher is the key instrument, data collection techniques are carried out by triangulation (combination), data analysis is inductive/qualitative, and the results of qualitative research emphasize meaning rather than generalization. Qualitative descriptive research aims to describe, depict, explain, explain and answer in more detail the problems to be studied by studying as much as possible an individual, a group or an event. The results of the study show that the Calculation of Income Tax Article 21 Withholding by the WiN Partner Tax Consultant Office, Makassar Branch, is in accordance with PP No. 58 of 2023. The calculation is based on the amount of gross income of one month from employees multiplied by the TER rate, without using the PTKP rate according to the harmonization law.